Identifying Key Prognostic Indicators for Relapse and Chronic Epilepsy in Autoimmune Encephalitis: Insights from a Multicenter Retrospective Study - Lai Q; Chen Y; Wang W; Lian Z; Liu T; Wen C (Journal of Inflammation Research)
Qingwei Lai,1,* Yue Chen,1,* Wei Wang,2,* Zhangxu Lian,3,* Tengfei Liu,4 Chunmei Wen5 1Department of Neurology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of China; 2Department of Neurology, Yancheng First People’s Hospital, Yancheng, People’s Republic of China; 3Department of Neurology, Xuzhou Central Hospital, Xuzhou, People’s Republic of China; 4Department of Neurology, Xuzhou Mining Group General Hospital, Xuzhou, People’s Republic of China; 5Department of Neurology, Yancheng Third People’s Hospital, Yancheng, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingwei Lai, Department of Neurology, Affiliated Hospital of Xuzhou Medical University, 99 West Huaihai Road, Xuzhou, Jiangsu, 221002, People’s Republic of China, Tel +8651685802193, Email lqw8696@163.comObjective: The aims of this study were to investigate clinical factors associated with encephalitis relapse and chronic epilepsy development, and to evaluate the effectiveness of immunotherapy on encephalitis relapse.Methods: Patients with autoimmune encephalitis diagnosed as positive for neuronal surface antibodies in five general hospitals were included. A minimum 12-month follow-up period was conducted, and binary logistic regression analysis was used to identify predictors of encephalitis relapse and chronic epilepsy development. Additionally, decision curve analysis (DCA) was employed to assess the clinical net benefit of predicting encephalitis relapse and chronic epilepsy.Results: The study encompassed 65 patients with autoimmune encephalitis. The one-year relapse rate for encephalitis was 13.9%. The CASE score (P=0.045) was associated with encephalitis relapse, with subsequent immunotherapy proving beneficial in enhancing outcomes. Chronic epilepsy prevalence at one year was 26.2%, particularly higher among patients with positive LGI1 antibodies. Although adjustments in antiseizure medications were partially effective, 41.2% of patients developed drug-resistant epilepsy (DRE). DCA confirmed that the predictive models provided significant net clinical benefit in assessing the risk of encephalitis relapse and chronic epilepsy. Notably, the presence of diffuse cortical atrophy, medial temporal lobe atrophy, or cerebellar hemisphere atrophy was linked to relapsing encephalitis and chronic epilepsy.Conclusion: Most cases of autoimmune encephalitis are effectively managed, however, a minority of patients experience relapse or chronic epilepsy. The CASE score and LGI1 antibodies are independent risk factors for encephalitis relapse and chronic epilepsy development, respectively. Immunotherapy remains beneficial for relapsing patients, yet a portion may progress to DRE. Individuals with relapses and chronic epilepsy are predisposed to the development of cortical, temporal lobe, and cerebellar atrophy.Keywords: autoimmune encephalitis, relapse, chronic epilepsy, immunotherapy, prognosis